A társadalmi mozgalmak szerepe a demokratikus politikai rendszer intézményesedésének folyamatában Magyarországon (Szociológiai Szemle, 2024)
The mobilization and protest of social movements is not a new phenomena in Hungary. There were social mobilizations and protests also in the time of crisis of the Kádár-regime. In the new democracy the movements and conflict potentials has been changed and restructured. In a pluralist democracy, there is no political space for the civil right „opposition" of the communist systems, with its „second, samizdat publicity". Despite of this fact, there are still civil right movements acting against racism, and other forms of injuries against civil rights, like Amnesty International, Raoul Wallenberg Association, the „Democratic Charter". Former opposition groups are institutionalized in the new Hungarian democracy in the organizational forms of political parties.The older generation of the Hungarian opposition, from the seventies established the party called „Alliance of the Free Democrats". The younger generation of the opposition, from the eighties founded the party called „Alliance of the Young Democrats”. Especially the younger generation of the Hungarian opposition has been supported in its political protest by the ecology and peace movements, and it was rooted in the movement for the self-government of the student hostels. All these movements, ecology, peace and students have rather specific functions in the new democracy, and they are less relevant for the political mobilization today.New conflicts of the new political system raised new mobilizations and protests. The „taxi driver blockade" in the October of 1990 was a nation-wide protest movement against the drastic raise of the fuel prizes, organized by the professional transporters, especially by the taxi drivers, but also enjoyed a broader social support against social consequences of the marketization. The taxi drivers organized blockades throughout the country and paralysed the transport system of Hungary for three days, until a compromise has been reached. Since 1991, the so called „Democratic Charter” an umbrella organization of different citizen's groups and organizations organize public protest against anti-democratic tendencies (racism, government control of the media) on a mass scale. This organization has bees supported also by some of the political parties of the opposition.In 1992-1993 an association called „Society of People Under the Living Standard" organized nationwide campaigns against the general introduction of VAT and the „unsocial” character of governments economic policy. This movement is exhausted after the introduction of VAT, but despite this fact the conflict and protest potential of socially disadvantaged groups in Hungary is still there. The „media war", the conflict about the governmental control over public medias raised political protests of both sides; first the pro-governmental „national radicals”, after the government's interventionist policy in the medias the liberal organizations protested against the media policy with demonstrations, subscriptions, rallies. The protest potential of agrarian interest organizations and of trade unions is also there in Hungary.New characteristics of political protest compared with the Kádár regime are, that public, legal mobilization and protest are allowed. Before, the regime tried to hinder networking, publicity protest and international relations of protest organizations. Now in the framework of freedom of association and gathering, legal and public networking, resource mobilization and political protest are widely accepted phenomena’s and used form of action. Beyond the framework of the legal protests, demands for civil disobedience has been articulated by different groups. Violent and illegal forms of political protest are rare in Hungary, violent conflicts with the police on demonstrations are marginal in the last four years.